2014
DOI: 10.1111/joic.12156
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Device Closure of Patent Ductus Arteriosus with Pulmonary Artery Hypertension: Long‐Term Results

Abstract: Device closure of PDA with PAH is feasible, safe in all age groups. Temporary PDA occlusion with device is effective and time saving for evaluating pulmonary vascular reactivity. Device embolization in aorta is higher with severe PAH. Novel method of retrieval is effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…As the name implies, the AMVSDO is not especially made for PDA closure and therefore comes with a larger, more bulky shape, suitable for muscular ventricular septal defects . Device size, however, and consecutive risk of obstruction of the pulmonary artery or the aorta are a major concern in percutaneous PDA closure especially in smaller children <10 kg with moderate to large ducts . According to Moysich et al the Nit‐Occlud PDA‐R ® device may be an efficient option in such cases due to its high flexibility and low profile of the aortic retention disc .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…As the name implies, the AMVSDO is not especially made for PDA closure and therefore comes with a larger, more bulky shape, suitable for muscular ventricular septal defects . Device size, however, and consecutive risk of obstruction of the pulmonary artery or the aorta are a major concern in percutaneous PDA closure especially in smaller children <10 kg with moderate to large ducts . According to Moysich et al the Nit‐Occlud PDA‐R ® device may be an efficient option in such cases due to its high flexibility and low profile of the aortic retention disc .…”
Section: Discussionsupporting
confidence: 72%
“…Closure of very large PDA with apparent PAH is still under discussion in an otherwise famous history of transcatheter PDA closure . In large ductus measuring 4 to > 22 mm interventionalists have achieved closure with coils, without or in combination with specific ductal occluder, septal occluder and also muscular ventricular septal occluder . To offer adequate treatment options, even an off‐label use of commercially available devices may be necessary in selected cases.…”
Section: Discussionmentioning
confidence: 99%
“…PDA device embolisation to the aorta is often associated with pulmonary arterial hypertension, or is secondary to improper device position with the pulmonary end of the device remaining within the body of the duct and not extending into the pulmonary artery. [6][7][8] Vijalalaxmi et al have reported embolisation in eight of 1325 patients (3.3%) of PDA with pulmonary hypertension. 7 Khan et al reported device embolisation to the aorta (6/4 ADO) following improper positioning of the device prior to release.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Vijalalaxmi et al have reported embolisation in eight of 1325 patients (3.3%) of PDA with pulmonary hypertension. 7 Khan et al reported device embolisation to the aorta (6/4 ADO) following improper positioning of the device prior to release. 8 In contrast to cases of PDA device embolisation reported in literature, both our cases were unique in that pulmonary arterial pressures were normal and initial device position on angiography appeared optimal.…”
Section: Discussionmentioning
confidence: 99%
“…If increased pulmonary artery pressure (mean pressure > 25 mmHg) was recorded, flows and resistances in the pulmonary and systemic circulations were calculated. Pulmonary vascular reactivity was assessed as needed, using vasodilating agents (nitric oxide and 100% oxygen) and by temporary test occlusion of the PDA with a sizing balloon [9]. Next, a catheter was introduced through the femoral vein and passed through the pulmonary artery and PDA to the descending aorta and then exchanged over a guidewire for a long sheath of adequate size.…”
Section: Description Of the Proceduresmentioning
confidence: 99%